Ecosystem services assessment of the Jardín Botánico de Bogotá (2024)
The green areas of Bogotá provide well-being to residents and visitors of the Colombian capital. The ecological infrastructure of Jardín Botánico de Bogotá (JBB) allows its visitors to enjoy various ecosystem services. This study aims to estimate the monetary value of the ecosystem services provided by the JBB. The research was conducted at the JBB. A forest inventory was performed for the biophysical valuation, including individuals with a diameter at breast height (DBH) greater than 10 cm. Total height and DBH were recorded for each individual. The timber volume and carbon captured in the aerial biomass of each individual and species were determined. Carbon capture was calculated using the allometric formula for montane humid forests. The provisioning ecosystem service of timber was valued based on the timber volume and the domestic timber price of US$270.9 per cubic meter. The monetization of carbon capture included the value of carbon credits from the European Union, used to determine the atmospheric regulation ecosystem service. The travel cost methodology involved surveying JBB visitors to determine the recreational cultural ecosystem service. Visitors were asked about their origin and visit frequency. The analysis included the entrance fee of US$1.05 and visitors’ meal costs. Finally, the cost/benefit monetary value was aggregated with the travel cost monetary value to calculate the total economic value (TEV). The BBG provides ecosystem services with a TEV of US$68,517,466.50 per year.